2018
DOI: 10.2147/jpr.s158793
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric properties of the electronic Pain Assessment Tool (ePAT) for aged-care residents with moderate to severe dementia

Abstract: PurposeAccurate pain assessment is critical to detect pain and facilitate effective pain management in dementia patients. The electronic Pain Assessment Tool (ePAT) is a point-of-care solution that uses automated facial analysis in conjunction with other clinical indicators to evaluate the presence and intensity of pain in patients with dementia. This study aimed to examine clini-metric properties (clinical utility and predictive validity) of the ePAT in this population group.MethodsData were extracted from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 26 publications
(69 reference statements)
0
28
0
3
Order By: Relevance
“…(82) Yet, this was possibly minimised in our study by the familiarity of consultants with residents' behaviours, and the use of a robust, systemised and structured pain assessment, which was validated in RACHs. (35,36,71,83) This assessment puts less emphasis on changes in physiological indicators (e.g. temperature), because these can be influenced by confounders (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…(82) Yet, this was possibly minimised in our study by the familiarity of consultants with residents' behaviours, and the use of a robust, systemised and structured pain assessment, which was validated in RACHs. (35,36,71,83) This assessment puts less emphasis on changes in physiological indicators (e.g. temperature), because these can be influenced by confounders (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The study demonstrated the high accuracy, sensitivity and specificity of the App in detecting pain in individuals with dementia. It also demonstrated the excellent clinical utility of the App for pain screening and case finding, as indicated by Mitchell's Index (Table 3 ) (Hoti et al, 2018 ).…”
Section: Methods and Resultsmentioning
confidence: 95%
“…To date, three studies about the PainChek™ App have been published (Table 3 ; Atee et al, 2017a , b ; Hoti et al, 2018 ). In blind comparisons with the Abbey Pain Scale, PainChek™ has been clinically evaluated in aged care residents with moderate to severe dementia in two prospective observational studies (Atee et al, 2017a , b ).…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations